WALI HAKIM DALAM PELAKSANAAN PERKAWINAN MENURUT PRESPEKTIF HUKUM ISLAM DAN HUKUM POSITIF (Studi kasus KUA Kecamatan Wonoayu kabupaten Sidoarjo) - Mas Habib Syaifulloh; Dzulfikar Rodafi Rodafi; Dwi Ari Kurniawati (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2020)
AbstractMarriage in the Indonesian legal system, especially for those who adhere to the Islamic religion requires a guardian in marriage. These obligations can be seen in the regulations issued by the government, including in the Compilation of Islamic Law Article 19 to Article 23 and Minister of Religion Regulation Number 11 Year 2007 regarding Marriage Registration Article 18. The necessity for the guardian in marriage is basically an agreement of the majority of scholars, except Madzhab Hanafiyah which does not require a guardian for women, especially if the woman has grown up and is able to account for every word and deed. (1) What is the Position of Judge Guardian in Marriage in the perspective of Islamic Law and Positive Law in KUA of Wonoayu District and (2) How is the Legality of Judge Guardian in Perspective of Islamic Law and Positive Law in KUA of Wonoayu Sidoarjo District ?. This study aims to determine as clearly as possible the position of the guardian judge in KUA Wonoayu District, and to determine the validity of the guardian judge according to positive law and Islamic law. The research method used is the field research method where this research is descriptive in nature. Data collection method is done through observation, and interviews. Source of data used comes from primary data and secondary data. Analysis of the data used is qualitative data analysis with an inductive thinking approach. Based on the results of the study concluded that, the position of guardian judge in KUA Wonoayu District Regulation of the Minister of Religion Number 2 of 1987 concerning the Guardian Judge, Regulation of the Minister of Religion Number 11 of 2007 concerning Marriage Registration, KHI Article 23 paragraph 2 and Al-Quran Surah 2 Al-Baqarah paragraph 232 and authorize the KUA to appoint a guardian of the judge as marriage guardian. the position of the judge's guardian as a guardian in marriage is considered valid according to positive law and Islamic law based on positive law namely KHI Article 23 paragraph 2 where the change from the guardian nasab to the judge's guardian is because the trustee is made after the decision of the Religious Court regarding the guardianship of the guardian. based on Islamic law namely Al-Qu'ran 24th letter An-Nur verse 32 there is an order to marry men and women who are alone who deserve to be married, then the second letter to Al-Baqarah verse 232. So in this case the KUA should carry out the marriage contract in accordance with the provisions of the law, to the bride and groom to always ask for permission from the trustees of the nasab and the trustees of the nasab to achieve mutual benefit. Keywords: guardian judge, marriage, law